Black beauty eaudiobook The autobiography of a horse. - Sewell, Anna (Blackstone Audio, Inc., and Buck 50 Productions, LLC, 2011)
From its first publication in 1877, Black Beauty has been one of the best-loved animal stories ever written. The dramatic and heartwarming tale is told by the magnificent black horse himself, from his idyllic days on a country squire's estate to his harsh fate as a London cab horse and his merciful rescue by two kindly old ladies. Filled with vivid anecdotes about animal intelligence, the novel derives a special magic from the love of all creatures, great and small, apparent on every page. But the book's lasting impact comes from its descriptions of a human society struggling to find the goodness within itself and its plea for kindness to all creatures—a message so powerful that this favorite classic began a crusade for animal welfare that continues to this day.